2016
DOI: 10.1681/asn.2014111144
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte Purinergic P2X4 Channels Are Mechanotransducers That Mediate Cytoskeletal Disorganization

Abstract: Podocytes are specialized, highly differentiated epithelial cells in the kidney glomerulus that are exposed to glomerular capillary pressure and possible increases in mechanical load. The proteins sensing mechanical forces in podocytes are unconfirmed, but the classic transient receptor potential channel 6 (TRPC6) interacting with the MEC-2 homolog podocin may form a mechanosensitive ion channel complex in podocytes. Here, we observed that podocytes respond to mechanical stimulation with increased intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 59 publications
5
33
0
Order By: Relevance
“…However, Forst and colleagues found that upon mechanical stimulation podocytes release ATP, which stimulates the P2X purinoceptor 4 (P2X4) and eventually results in Ca 2+ influx without the contribution of TRPC6 (Forst et al . ). These findings demonstrate that a mechano‐gated TRPC6‐independent Ca 2+ entry pathway exists in podocytes.…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 97%
“…However, Forst and colleagues found that upon mechanical stimulation podocytes release ATP, which stimulates the P2X purinoceptor 4 (P2X4) and eventually results in Ca 2+ influx without the contribution of TRPC6 (Forst et al . ). These findings demonstrate that a mechano‐gated TRPC6‐independent Ca 2+ entry pathway exists in podocytes.…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 97%
“…In addition, TRPC channels did not play an important role. Instead ATP‐gated P 2 X 4 cation channels were identified as pivotal mechanotransducers in podocytes while mechanosensors in these cells have not been identified yet . Since vascular autoregulation is of paramount importance in physiology, one may speculate that several yet to identify backup‐strategies have evolved which cooperate to constantly maintain blood flow, perfusion pressure and vascular tone.…”
Section: Perspectivementioning
confidence: 99%
“…Such endothelial dysfunction would impair BP regulation through the pressure natriuresis response (Ivy and Bailey ), but P2X4 is also expressed in glomerular podocytes(Forst et al. ) and throughout the renal tubule (Turner et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…P2X4 À/À mice are hypertensive and have an impaired endothelial production of nitric oxide in response to increased vascular flow (Yamamoto et al 2006). Such endothelial dysfunction would impair BP regulation through the pressure natriuresis response (Ivy and Bailey 2014), but P2X4 is also expressed in glomerular podocytes (Forst et al 2016) and throughout the renal tubule (Turner et al 2003). Whether loss of renal tubular P2X4 contributes to hypertension in P2X4 À/À mice is not known.…”
Section: Introductionmentioning
confidence: 99%